An Analysis of English Student Needs in the Development of a Hybrid Learning Teaching Material Model Based on Religious Moderation Values - Anggaira, Aria Septi; Sari, Yeasy Agustina (Anglophile Journal, 2023)
Technology plays a very important role in today's learning process. Online learning is not an option anymore but an obligation that must be carried out, especially during the Covid-19 Pandemic. Hybrid learning is one of the online learning that is widely used at all levels of education. This research is the initial research from development research that will develop a hybrid learning model based on religious moderation values in the teaching media course. The respondents in this study were 89 students majoring in English education at Institut Agama Islam Negeri (IAIN) Metro Lampung. The data was obtained through the results of the questionnaire. The result showed that the students needed a hybrid learning teaching material model based on religious moderation values in the teaching media course. It was evidenced by the results of the questionnaire, namely as many as 80% of students state that they need a hybrid learning teaching material model based on religious moderation values in the eyes of teaching media lectures. Keywords: Development of Hybrid Learning, Religious Moderation Values, Teaching Material